Fruit Beer with the Bisucciu Sardinian Apricot Cultivar (Prunus armeniaca L.): A Technological and Analytical Approach - Antonio Valentoni; Riccardo Melis; Manuela Sanna; Maria Cristina Porcu; Margherita Rodolfi; Angela Braca; Angela Bianco; Giacomo Zara; Marilena Budroni; Roberto Anedda; Daniela Piras; Luca Pretti (Fermentation, 2023)
The aim of this work was to test native microbial strains and fruits for brewing, with a multidisciplinary approach for a sustainable production linked to the territory. Pediococcus acidilactici B5 and Hanseniaspora uvarum L2 strains were isolated from apricot Bisucciu fruits, a Sardinian local variety (Prunus armeniaca L.), and P. acidilactici B5 was used to ferment a sterile apricot Bisucciu puree, which was then added to a malt wort. The H. uvarum L2 strain and the industrial yeast Saccharomyces cerevisiae US-05 were used sequentially to ferment a portion of this wort (M2); a control was carried out with an industrial yeast, S. cerevisiae T-58 (T58). Beer standard quality parameters were studied and a sensorial analysis performed in the beers obtained from the two fermentations. Intermediate and end molecular products were characterized by proton Nuclear Magnetic Resonance (1H NMR) for glucidic, organic acids and amino acids and by Gas Chromatography–Mass Spectrometry (SPME/GC/MS) for volatile profiles. M2 and T58 samples showed differences in color, foam stability and in the carbohydrates, acids and amino acids profiles. The highest concentrations of ethyl acetate were found in M2, whereas a high concentration of 3-methylbutan-1-ol characterized T58. Sensory analysis highlighted differences in flavor, astringency and balance between the two beers studied.